"How people read and write and they don't even notice": everyday lives and literacies on a Midlands council estate. (3rd March 2014) - Jones, Susan
Abstract This article presents data from a British Academy‐funded study of the everyday literacy practices of three families living on a predominantly white working‐class council housing estate on the edge of a Midlands city. The study explored, as one participant succinctly put it, "how people read and write and they don't even notice". This alludes to the ways in which everyday practices may not be recognised as part of a dominant model of literacy. The study considered too the ways in which these literacy practices are part of a wider policy context that also fails to notice the impact of austerity politics on everyday lives. An emphasis on quantitative measures of disadvantage and public discourse which vilifies those facing economic challenge can overshadow the resilience and resourcefulness of individuals and families in making meaning from their experiences. Drawing together consideration of everyday lives and the everyday literacies which are part of them, this article explores the impact of the current policy context on access to both economic and cultural resources, showing how literacy, as part of this context, should be recognised as a powerful means not only of constricting lives but also of constructing them.